An older person as a human in the execution of imprisonment in Czech prisons – exploratory probe - Stárek, Lukáš (Interacción y Perspectiva, 2024)
The eldering of society is expected to see growth in elderly people conducting crime and in the execution of imprisonment processes not only in the Czech Republic. Based on evidence from published literature and conducted exploratory probes, we highlight the chance and need for more attention paid to older people; we call for a change of attitude towards the eldering population and mainly towards older people in the execution of imprisonment. The paper aims to shed light in theory and through field notes on specific related towards this group of people. The six interviews were conducted, and personal files were reviewed to bring interesting insights and characteristics about this group. With regard to the growing population of older people in the execution of imprisonment, there is an obvious need to analyze this group in more depth, not only through the lens of social science but also by providing deeper support and care. Further, the eldering process in imprisonment demands a bigger need for employers’ qualification and ability to provide adequate care. Plus, there is a significant need to reorganize funding.